Effect of virtual reality educational program on critical thinking disposition among nursing students in Egypt: a quasi-experimental pretest–posttest design - Mona Ahmed Mohamed Gabr; Wafaa Fathi Sleem; Nehad Saad El-wkeel (BMC Nursing)
Abstract Background Education has continuously evolved to keep pace with advancements in information technology. Virtual reality (VR) has emerged as an innovative and effective learning approach that enhances student engagement, particularly in developing problem-solving and critical thinking skills. Since its introduction in the early 1980s, VR has gained increasing attention in nursing education due to its potential to improve learning outcomes and skill acquisition. However, there is a need for further research to explore its impact on critical thinking disposition among nursing students. Methods This quasi-experimental pretest-posttest study was conducted with a convenience sample of 190 nursing students from Damietta University’s Faculty of Nursing. Participants were assessed on their critical thinking disposition and VR-related knowledge at three time points: before the intervention, immediately after, and two months post-intervention. Aim: The VR-based educational program aimed to improve students’ critical thinking disposition and assess their knowledge of virtual reality before, during, and after the program. Results A statistically significant improvement in students’ mean scores for critical thinking disposition was observed across all evaluations (p < 0.001). The effect size (η²p ≥ 0.14) indicated a substantial impact, reinforcing the effectiveness of the VR-based educational program in fostering higher-order cognitive skills. Additionally, students demonstrated increased retention of VR-related knowledge when assessed immediately after the program and again after two months. Conclusions This study highlights the transformative potential of VR as an educational tool in nursing. VR-based learning promotes active engagement, knowledge retention, and skill development in a safe and controlled environment. By integrating VR programs into nursing education, institutions can enhance students’ critical thinking, collaboration, and communication skills, ultimately preparing them for real-world clinical practice. Given these findings, educational institutions should consider incorporating VR technology to support the continuous development of essential nursing competencies. Trial registration This study is formally registered on ClinicalTrials.gov (Identifier Code: NCT06622811; Registration Date: 01/10/2024).